Communication—Electrodeposition of Al-Sc Alloys from LiCl-KCl Molten Salt Containing AlCl3 and ScCl3. Issue 8 (24th August 2021) - Hirai, Tomoki; Matsushima, Hisayoshi; Ueda, Mikito
Abstract : To investigate co-electrodeposition of Al and Sc ions, voltammogram measurements were carried out in LiCl-KCl molten salt containing AlCl3 and ScCl3 at 723 K. In the voltammogram measurements, a cathodic current of Al ions and formation of Al-Sc alloys were observed from 0 V and −0.2 V vs Al/Al(III), respectively. Sponge-like electrodeposit formed on the Cu substrate cathode under the condition of a constant potential electrolysis at −0.4 V. The contents of Al and Sc in the electrodeposit were 73.6 and 8.8 at% by EDS analysis. The X-ray diffraction pattern of the electrodeposit fits the patterns of Al and Al3 Sc.